Secret teachings of a comic book master : the art of Alfredo Alcala - MacDonald, Heidi; Yeh, Phil, 1954- (Mineola, New York : Dover Publications, Inc., 2015)
"Alfredo Alcala is one of the most disciplined and perceptive artists inking in comics. The years of distinguished work have earned Alfredo a special place in comics history."-- Gil Kane. In the late 1960s, an extremely talented group of Filipino illustrators took the American comic book industry by storm-- and Alfredo Alcala led the way, working for both Marvel and DC on such popular characters as Conan the Barbarian and Batman. This unique work is loaded with amazing art and pointers on observational methods, composition, and other techniques. In addition to insightful interviews with Alcala, the book features pages from his groundbreaking masterwork, Voltar, which was hailed as a new concept in comic book form, an epic in narrative art, and a milestone in sequential art illustration. Students, professionals, teachers, and fans will treasure this inspiring volume and its insider's look at comic book artistry"--
Keywords: Alcala, Alfredo P. -- Criticism and interpretation; Comic books, strips, etc. -- History and criticism; Comic books, strips, etc. -- Technique; Narration (Rhetoric); Cartoonists -- Philippines